Seratrodast inhibits ferroptosis by suppressing lipid peroxidation - Tschuck, Juliane; Tonnus, Wulf; Gavali, Shubhangi; Kolak, Andrea; Mallais, Melodie; Maremonti, Francesca; Sato, Mami; Rothenaigner, Ina; Friedmann Angeli, José Pedro; Pratt, Derek A.; Linkermann, Andreas Günter; Hadian, Kamyar (Cell death & disease, 2024)
Ferroptosis is a regulated and non-apoptotic form of cell death mediated by iron-dependent peroxidation of polyunsaturated fatty acyl tails in phospholipids. Research of the past years has shed light on the occurrence of ferroptosis in organ injury and degenerative diseases of the brain, kidney, heart, and other tissues. Hence, ferroptosis inhibition may prove therapeutically beneficial to treat distinct diseases. In this study, we explored the ferroptosis-modulating activity of seratrodast, an inhibitor of thromboxane A2 (TXA2) receptor, which is approved in some countries for the treatment of asthma. Interestingly, seratrodast suppressed ferroptosis, but not apoptosis and necroptosis; thus, demonstrating selective anti-ferroptotic activity. While seratrodast itself does not inhibit lipid peroxidation, it exhibits potent radical-trapping antioxidant activity upon reduction to its corresponding hydroquinone form—analogously to ubiquinone and vitamin K. Importantly, seratrodast ameliorated the severity of renal ischemia-reperfusion injury in mice. Together, this study provides a drug repurposing case, where seratrodast—a marketed drug—can undergo fast-forward preclinical/clinical development for the inhibition of ferroptosis in distinct degenerative diseases.
Gesehen am 14.04.2025